Resisted and assisted methods of speed development - Faccioni, A.
The purpose of this study was to determine whether the use of resisted training (speed sled), over-speed or supra-maximal training (speed belt), or a combination of both methods affects the development of speed over 20m, 40m, and 60m, greater than a control group. The results indicate that sprint training using these devices has a significant effect upon speed development over a variety of distances. The Assisted/Resisted group showed significant improvements over all 3 distances from pre to post testing, with the resisted group showing improvements over 20m and 60m that were also significant. The Control and Assisted group showed significant improvements over 60m only.